Description of the final instar nymph of Homeoura nepos (Selys, 1876) (Odonata: Coenagrionidae) - Tennessen, Kenneth J. (Zootaxa, 2009)
The description of the nymph of Homeoura nepos (Selys, 1876) by Calvert (1948) was based on a single, immature specimen from São Paulo, Brazil which lacked gills. The nymphs of H. chelifera (Selys) and H. lindneri (Ris) were described by Lozano et al. (2009), who considered Calvert’s description of the nymph of H. nepos doubtful.